La Macédoine des Jeunes-Turcs et l’hellénisme à travers la presse grecque : 1908-1910 - Sia Anagnostopoulou (Cahiers Balkaniques)
Between July 1908 and the beginning of 1910, the Greek press, towards the Young Turks, from enthusiasm changed to suspicion and radical criticism. Its first hopes are in a liberty and equality allowing to the helleno-ottomanism a greek-turkish domination which could push away any bulgarian hold over Macedonia, that is to say the main concern of Greek nationalists in 1908. In spring 1909, the Greek press understands that “helleno-ottomanism” may lead to “turkism”, its enthusiasm for the Young Turks soon and quickly falls down, salvation won’t come from “ottomanism” but from Greece itself and from its military preparation versus the Turks, for ever “barbarians”.